2022
DOI: 10.1556/2006.2021.00086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frontostriatal circuits in adolescent nicotine addiction and internet gaming disorder

Abstract: Background Recently, there has been significantly increased participation in online gaming and other addictive behaviors particularly in adolescents. Tendencies to avoid social interaction and become more involved in technology-based activities pose the danger of creating unhealthy addictions. Thus, the presence of relatively immature cognitive control and high risk-taking properties makes adolescence a period of major changes leading to an increased rate of emotional disorders and addiction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 119 publications
(194 reference statements)
0
7
0
Order By: Relevance
“…Other authors have cited a need for studying girls and women with IGD 33,34 . Some authors have observed that men show a greater activation of the thalamus, compared with women, which might make them more susceptible to developing IGD than women 35,36 . Moreover, abnormal frontoparietal/cingulo-opercular network connections have been described in males with IGD, suggesting another possible mechanism for male vulnerability to develop IGD 37 .…”
Section: Neuroimaging Correlates Of Gaming and Igdmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have cited a need for studying girls and women with IGD 33,34 . Some authors have observed that men show a greater activation of the thalamus, compared with women, which might make them more susceptible to developing IGD than women 35,36 . Moreover, abnormal frontoparietal/cingulo-opercular network connections have been described in males with IGD, suggesting another possible mechanism for male vulnerability to develop IGD 37 .…”
Section: Neuroimaging Correlates Of Gaming and Igdmentioning
confidence: 99%
“…33,34 Some authors have observed that men show a greater activation of the thalamus, compared with women, which might make them more susceptible to developing IGD than women. 35,36 Moreover, abnormal frontoparietal/cingulo-opercular network connections have been described in males with IGD, suggesting another possible mechanism for male vulnerability to develop IGD. 37 Marraudino et al, 38 in their review, also examined sex/gender differences identified at the neurobiological level in individuals with IGD.…”
Section: Neurobiological Sex/gender Differencesmentioning
confidence: 99%
“…The altered functional connectivity of thalamic subregions-cortical circuits involved in the reward and withdrawal symptoms was shown in drug abusers (Zhang et al ., 2021 ). Similar neuroplastic changes including altered gray matter volume and connectivity of striatal regions and circuits involved in reward and cognitive control were also detected for internet gaming disorder (IGD) (Qin et al ., 2020 ; Zhou et al ., 2020 ; von Deneen et al ., 2022 ; Yu et al ., 2022 ). IGD has been recently included as a mental disorder in the ICD-11 and DSM-V (Grant and Chamberlain, 2016 ).…”
Section: The Corticostriatal Circuits Plasticity Changes In Addictionmentioning
confidence: 99%
“…Neuroimaging technology provides us with the scientific and intuitive methods (Canario et al ., 2021 ; Dong et al ., 2022 ) to study brain mechanism of addiction noninvasively, which has built a bridge between addictive behavior and neural mechanism. Brain structural and functional plasticity has been studied in addiction, such as dysfunctions in the dopaminergic system (Liu and Li, 2018 ) and corticostriatal circuits (Volkow and Morales, 2015 ; von Deneen et al ., 2022 ). Notably, the brain activation and connectivity patterns in abstainers exposed to drug cues and their associations with future relapse risk were assessed using functional imaging (Grüsser et al ., 2004 ; Beck et al ., 2012 ).…”
mentioning
confidence: 99%
“…Better emotional regulation strategies have been linked to positive and healthy mental states in adolescents ( Houck et al, 2016 , Te Brinke et al, 2021 ). In contrast, adolescents with poor emotional regulation are more likely to adopt maladaptive coping strategies (such as avoidance and withdrawal), which could result in the development of various addictive behaviors ( Hudak et al, 2022 , Vintro-Alcaraz et al, 2022 , von Deneen et al, 2022 ) and emotional disorders ( Miklowitz et al, 2022 , Price et al, 2022 ). Although SMAs do not involve substance intake, they may influence dopaminergic and other systems, and may help adolescents relieve stress and manage negative emotions in the short term ( Dong et al, 2021 , Laier and Brand, 2018 ).…”
Section: Introductionmentioning
confidence: 99%